Green Synthesis of Silver Nanoparticles (AgNPs) Using Polyvinyl Alcohol (PVA)-Modified Andrographis paniculata Leaf Extract for Mercury (Hg2+) Colorimetric Sensing - Arah Guntur Guntur; Akmalia Dinda Oktavianta Oktavianta; Ketut Sumada; Sani Sani; Caecilia Pujiastuti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Mercury (Hg2+) contamination is a serious environmental issue due to its toxicity and persistence. This study reports the green synthesis of silver nanoparticles (AgNPs) using Andrographis paniculata leaf extract with poly(vinyl alcohol) (PVA) as a capping agent, and evaluates their application as a colorimetric sensor for Hg2+. detection. AgNPs were synthesized using varying AgNO3 (0.5–2.5 mM) and PVA (0.1–1.0%) concentrations and characterized by FTIR and UV–Vis spectroscopy. FTIR confirmed functional groups involved in the reduction of Ag+ to Ag0, while UV–Vis spectra showed LSPR peaks at 411–448.5 nm, indicating successful nanoparticle formation. The optimum condition was obtained at 2 mM AgNO3 and 0.4% PVA, with a maximum absorbance of 0.710 at 435.5 nm. The AgNPs exhibited a clear colorimetric response to Hg2+, changing from yellowish-brown to colorless. These results highlight the potential of A. paniculata-based AgNPs as an eco-friendly and cost-effective sensor for mercury detection.